2018
DOI: 10.1002/adfm.201705183
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Performance Nanoengineered Graphene–Concrete Composites for Multifunctional Applications

Abstract: Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(113 citation statements)
references
References 23 publications
2
93
0
7
Order By: Relevance
“…The outstanding mechanical properties of single layer graphene, GnPs and GO, led to a new generation of improved plastic-based structural materials [17,142,143]. For example, these 2D carbon-based fillers are attractive for the realization of next generation sporting goods [144], concrete [145], anti-corrosion coatings [146], automotive lightweight components [147], structural elements in aerospace [148], and wind turbine designs [149]. In particular, GnP powder is already produced at large scales and at a low price compared with single-layer graphene, and as such, is more appealing for the composite market [150].…”
Section: Advanced Reinforced Graphene Nanoplatelet-based Bio-nanocompmentioning
confidence: 99%
“…The outstanding mechanical properties of single layer graphene, GnPs and GO, led to a new generation of improved plastic-based structural materials [17,142,143]. For example, these 2D carbon-based fillers are attractive for the realization of next generation sporting goods [144], concrete [145], anti-corrosion coatings [146], automotive lightweight components [147], structural elements in aerospace [148], and wind turbine designs [149]. In particular, GnP powder is already produced at large scales and at a low price compared with single-layer graphene, and as such, is more appealing for the composite market [150].…”
Section: Advanced Reinforced Graphene Nanoplatelet-based Bio-nanocompmentioning
confidence: 99%
“…The re-sults show that the addition of 0.02wt% GO (by fly ash weight) significantly improves the mechanical properties and durability of the fly ash base polymer, and GO has the potential to improve the fixation of heavy metals in fly ash. Dimov et al [109] found that when water-stabilized graphene dispersion was added to concrete, its mechani-cal strength and impermeability were greatly improved. Its compressive strength and flexural strength were increased by 146% and 79.5%, water permeability was reduced by nearly 400%, and electrical and thermal properties were also found to be enhanced.…”
Section: Research Progress Of Graphene Modified Geopolymermentioning
confidence: 99%
“…A small amount of GNPs reduces the percentage of macropores, even though the total porosity is slightly affected suggesting a broader distribution of small gel pores in the composite. Moreover, during the hydration process, C-S-H particles bonded to graphene flakes act as a nucleation site and promote the growth of C-S-H gel with higher crystallinity degree [92]. Under this scenario, we can explain the increase of ionic conductivity in relation with the enhancement of ordered C-S-H gel that promote a smoother diffusion of water molecules through the porous network.…”
Section: Opc Opc/gnpsmentioning
confidence: 93%
“…A small amount of GNPs reduces the percentage of macropores, even though the total porosity is slightly affected suggesting a broader distribution of small gel pores in the composite. Moreover, during the hydration process, C-S-H particles bonded to graphene flakes act as a nucleation site and promote the growth of C-S-H gel with higher crystallinity degree [92]. Under this scenario, we can Trying to elucidate how the presence of graphene nanoplatelets affect conductivity in cement paste, we summarize the main results of this work: First we observed an enhancement of the electrical properties in the composite by means of impedance response study, while dielectric response investigation proved that the main mechanism of charge transport is water percolation.…”
Section: Opc Opc/gnpsmentioning
confidence: 99%